Case report: Susac syndrome—two ends of the spectrum, single center case reports and review of the literature - Cviková, Martina; Štefela, Jakub; Všianský, Vít; Dufek, Michal; Doležalová, Irena; Vinklárek, Jan; Herzig, Roman; Zemanová, Markéta; Červeňák, Vladimír; Brichta, Jaroslav; Bárková, Veronika; Kouřil, David; et al. (Frontiers in Neurology, 2024)
Susac syndrome is a rare and enigmatic complex neurological disorder primarily affecting small blood vessels in the brain, retina, and inner ear. Diagnosing Susac syndrome may be extremely challenging not only due to its rarity, but also due to the variability of its clinical presentation. This paper describes two vastly different casesone with mild symptoms and good response to therapy, the other with severe, complicated course, relapses and long-term sequelae despite multiple therapeutic interventions. Building upon the available guidelines, we highlight the utility of black blood MRI in this disease and provide a comprehensive review of available clinical experience in clinical presentation, diagnosis and therapy of this disease. Despite its rarity, the awareness of Susac syndrome may be of uttermost importance since it ultimately is a treatable condition. If diagnosed in a timely manner, early intervention can substantially improve the outcomes of our patients.